Desproporcionalidad en la sanción sobre difusión de contenido discriminatorio en la ley orgánica de comunicación - Guevara Cordero, Galo Daniel (2016)
The Organic Law of Communication penalizes the dissemination of discriminatory content. The sanction contains several provisions to protect the dignity of people. The establishment of this penalty is an economic fine that increases its value indefinitely, so it turns out to be disproportionate. It affects freedom of enterprise and freedom of speech collaterally. This article of the Communication Law, opposes the mandate of proportionality set out in Article 76.6 of the Constitution of the Republic of Ecuador. This work uses doctrine, the national legislation and jurisprudence of the Constitutional Court, in order to prove the hypothesis.